Volatility of FTSE Bursa Malaysia KLCI index and exchange rete around 2008 financial crisis - Lim, Xin Yi (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study examines the volatility of FTSE Bursa Malayisa KLCI (FBM KLCI) index and the association with the exchange rate around the 2008 financial crisis, with a sample of 1242 observations. This study employs event study methodology. More specifically, it employs the time series trend graph to examine the movement of the FBM KLCI index return, standard deviation to study the risk correlated with the fluctuation of price and Granger Causality test is employed to examine the causality of the variables. The findings show that FBM KLCI index return is more volatile and more risky during 2008 financial crisis. Moreover, there is no relationship between stock market return and exchange rate of return around the period of financial crisis. However, there is a bidirectional causality running the exchange rate returns of United States dollar to Malaysian ringgit and exchange rate of returns of Euro to Malaysian ringgit